Synthesis and Characterization of Corrosion Inhibitor Of 2-Amino 5-Oleyl-1, 3, 4-Thiadiazol in 1M HCL solution for Mild Steel - R.D, Pruthviraj.; S.D, Ashok. (IJRDO-Journal of Applied Science, 2016)
Novel corrosion inhibitor as a green chemical product namely derivative, 2-amino 5-oleyl1,3,4-thiadiazol(AOT) was synthesized by cyclization of oleic acid. AOT was evaluated as corrosioninhibitor for Mild Steel in 1M of Hydrochloric acid solution using Potentiodynamic andElectrochemical Impedance Spectroscopy (EIS) technique. Results obtained show that AOT acts as agood corrosion inhibitor for mild steel in 1M HCl solution.